Über die verwandtschaftliche Stellung des Cryptocephalus angaricus Franz (Coleoptera: Chrysomelidae). - Machatschke, Johann W. (Contributions to Entomology = Beiträge zur Entomologie, 1959)
There is stated the systematic position of Cryptocephalus angaricus Franz as that of a subspecies of Cryptocephalus regalis Gebler, which is widely distributed in the Far East, forming a superspecies (Rassenkreis) including: Cryptocephalus regalis regalis Gebler, Cr. regalis mutatus Kraatz, Cr. regalis cyanescens Weise, Cr. regalis angaricus Franz, and Cr. regalis sutschanus n. ssp., the latter being described here.Nomenclatural Actsangaricus Franz, 1949 (Cryptocephalus), stat. n. now sspec. of Cryptocephalus regalis Gebler, 1830sutschanus Machatschke, 1959 (Cryptocephalus regalis), sspec. n.